Development of Interactive Video Media Solfeggio Learning in Performing Arts Education Study Program, FKIP UNTAN - Zakarias Aria Widyatama Putra; Imam Ghozali; Mastri Dihita Sagala; Egi Putri Grandena (Universitas Negeri Surabaya, 2023)
This research is development of interactive video-based solfeggio learning media in the Performing Arts Education Study Program, FKIP, UNTAN. The purpose of the study is to produce products in the form of interactive video solfeggio learning media, test the feasibility of interactive video-based solfeggio learning media, and describe the response of educators and students to interactive video-based solfeggio learning media. The research method used 4D Thiagarajan research and development with stages of define, design, development, and dissemination. The subjects and research time of students in semesters 3-5 and will be held from July to September 2022. Data collection techniques use questionnaires and interviews. Research instruments are addressed to media and material validators and users by providing instrument questionnaires as well as criticism, input, and suggestions. Data analysis uses a Likerts scale. The results of research that interactive videos are very worthy of being used as a learning medium for solfeggio. Based on the results of media validation by students that solfeggio material can improve the ability to read block notation.